Clinicopathologic and Genomic Characterization of Inflammatory Myofibroblastic Tumors of the Head and Neck: Highlighting a Novel Fusion and Potential Diagnostic Pitfall. (December 2021) - Kerr, Darcy A.; Thompson, Lester D.R.; Tafe, Laura J.; Jo, Vickie Y.; Neyaz, Azfar; Divakar, Prashanthi; Paydarfar, Joseph A.; Pastel, David A.; Shirai, Keisuke; John, Ivy; Seethala, Raja R.; Salgado, Claudia M.; et al.
Abstract : Inflammatory myofibroblastic tumor (IMT) is a distinctive fibroblastic and myofibroblastic spindle cell neoplasm with an accompanying inflammatory cell infiltrate and frequent receptor tyrosine kinase activation at the molecular level. The tumor may recur and rarely metastasizes. IMT is rare in the head and neck region, and limited information is available about its clinicopathologic and molecular characteristics in these subsites. Therefore, we analyzed a cohort of head and neck IMTs through a multi-institutional approach. Fourteen cases were included in the provisional cohort, but 1 was excluded after molecular analysis prompted reclassification. Patients in the final cohort included 7 males and 6 females, with a mean age of 26.5 years. Tumors were located in the larynx (n=7), oral cavity (n=3), pharynx (n=2), and mastoid (n=1). Histologically, all tumors showed neoplastic spindle cells in storiform to fascicular patterns with associated chronic inflammation, but the morphologic spectrum was wide, as is characteristic of IMT in other sites. An underlying fusion gene event was identified in 92% (n=11/12) of cases and an additional case was ALK-positive by IHC but could not be evaluated molecularly. ALK represented the driver in all but 1 case. Rearrangement of ALK, fused with the TIMP3 gene (n=6) was most commonly detected, followed by 1 case each of the following fusion gene partnerships: TPM3 - ALK, KIF5B - ALK, CARS - ALK, THBS1 - ALK, and a novel alteration, SLC12A2 - ROS1 . The excluded case was reclassified as spindle cell rhabdomyosarcoma after detection of a FUS - TFCP2 rearrangement and retrospective immunohistochemical confirmation of rhabdomyoblastic differentiation, illustrating an important diagnostic pitfall. Two IMT patients received targeted therapy with crizotinib, with a demonstrated radiographic response. One tumor recurred but none metastasized. These results add to the growing body of evidence that kinase fusions can be identified in the majority of IMTs and that molecular analysis can lead to increased diagnostic accuracy and broadened therapeutic options for patients.